Decolonizing Academic Literacy with ተዋሕዶ/Tewahedo and Multiliteracies in Higher Education - Oscar Eybers (Genealogy, 2025)
This study proposes Tewahedo epistemology, an Ethiopian knowledge system grounded in the Ge’ez language, as a decolonial framework for re-visualizing academic literacy in higher education. Tewahedo, meaning “oneness” or “unity”, integrates multiliteracies—written, oral, spatial, and visual—within a communal and culturally embedded ethos through its Tergwame (ትርጓሜ) epistemes and Andǝmta (አንድምታ) traditions. The aim of the article is to challenge the dominance of skills-based literacy models by positioning Tewahedo as a decolonized alternative, emphasizing contextualized knowledge, communal meaning-making, and epistemic belonging. Through a literature review, the study explores Andəmta as a communal and dialogic system of knowledge sharing, rooted in Ge’ez and Amharic hermeneutics. This framework serves as a template for Africanizing and decolonizing contemporary academic literacy development. Findings reveal that Tewahedo epistemology offers ancient yet innovative strategies for fostering interpretive, explanatory, and multimodal competencies in academia. The study argues that adopting a unified Tewahedo-based academic literacy framework can cultivate intellectual agency, decolonize educational spaces, and center Indigenous Knowledge Systems. It calls for educational reforms that promote cultural diversity, legitimize Indigenous Knowledge Systems, and nurture academic belonging for students in multilingual and multicultural contexts.